Reoperative surgery for bilateral multinodular goitre in the era of total thyroidectomy - Vasica, G.; O'Neill, C. J.; Sidhu, S. B.; Sywak, M. S.; Reeve, T. S.; Delbridge, L. W. (British journal of surgery, 2012)
Background: Total thyroidectomy, rather than bilateral subtotal thyroidectomy, is now accepted as the preferred management for bilateral benign multinodular goitre (BMNG) in order to reduce the need for reoperative surgery. The aim of this study was to examine whether this approach has had an impact on presentation for bilateral reoperative thyroid surgery. Methods: This was a retrospective cohort study. The study group comprised patients presenting with recurrent BMNG who underwent bilateral reoperative thyroid surgery following previous bilateral subtotal or partial thyroidectomy. They were compared with patients undergoing unilateral reoperative thyroid surgery following previous lobectomy, and those undergoing primary total thyroidectomy for BMNG. Results: Between 1 January 1987 and 31 December 2009, 12 354 consecutive thyroid procedures were undertaken. Among those with BMNG, primary total thyroidectomy was undertaken in 3298 patients, unilateral reoperative thyroidectomy in 337 and bilateral reoperative thyroidectomy in 191. Presentations of patients with recurrent BMNG declined gradually over the study period following the change in policy from subtotal to total thyroidectomy; only five patients (representing less than 0·5 per cent of all thyroid surgery) underwent bilateral reoperative surgery for BMNG in the last year of the study. Four of these patients had their initial operation before 1987 and in another unit, whereas the remaining patient initially had surgery overseas. Conclusion: The introduction of a policy of initial total thyroidectomy for bilateral BMNG has essentially eliminated the need for bilateral reoperative surgery for recurrent goitre. Copyright © 2012 British Journal of Surgery Society Ltd. Published by John Wiley & Sons, Ltd. Has eliminated the need for reoperation